A GIS based approach to Holocene hydrology and social connectivity in the Gobi Desert, Mongolia. (September 2018) - Holguín, Leah R.; Sternberg, Troy
Abstract: This paper presents the results of a GIS derived drainage network, demonstrating a hypothesized model of the Ulaan Nuur paleo hydrological system in the Gobi Desert of Mongolia. Furthermore, this model was successfully used as a basis for field survey along the hypothesized southern edge of the paleo lake and associated paleo channels, which led to the discovery of four Neolithic period sites, several Neolithic surface scatters, and one later period cemetery. This allows for the establishment of a potential, viable route of movement between the Gobi Altai and Bayanzag, along the southern paleo hydrological system of Ulaan Nuur. This case study further demonstrates that through examination of paleo hydrological landscapes in the Gobi Desert, GIS hydrology modelling may provide a reliable methodology to locate sites in other arid and semi-arid environments, and enable further evaluation of their relationships to past watercourses.